Dinamika Gerakan Kharismatik dalam Gereja Mainstream Kontemporer: Analisis Teologis dan Implikasi Praktis - Sariyanto Sariyanto; Petrus Baela; Bendris Tazuno; Darius Sriyono (Journal Of Spirituality And Practical Theology, 2025)
The Charismatic Movement emerged in the mid-20th century under the influence of Pentecostalism, emphasizing direct experiences with the Holy Spirit through spiritual gifts such as speaking in tongues, divine healing, and prophecy. This movement has significantly impacted mainstream churches, particularly in theology, worship styles, and leadership. This study employs a qualitative method with a descriptive-analytical approach, analyzing theological, historical, and sociological sources on the Charismatic Movement's development and its effects on mainstream churches. Findings show that the movement has reshaped worship patterns, increased congregational participation, and influenced leadership by prioritizing direct encounters with the Holy Spirit. It has also sparked theological shifts, challenging churches to balance doctrinal traditions with dynamic faith expressions. In conclusion, the Charismatic Movement has become a transformational force, fostering spiritual renewal and greater congregational engagement in mainstream churches.